Therapeutic bispecific antibodies against intracellular tumor antigens. (10th July 2022) - Xu, Guanghui; Luo, Yuting; Wang, Hanbing; Wang, Yue; Liu, Baorui; Wei, Jia
Abstract: Bispecific antibodies (BsAbs)-based therapeutics have been identified to be one of the most promising immunotherapy strategies. However, their target repertoire is mainly restricted to cell surface antigens rather than intracellular antigens, resulting in a relatively limited scope of applications. Intracellular tumor antigens are identified to account for a large proportion of tumor antigen profiles. Recently, bsAbs that target intracellular oncoproteins have raised much attention, broadening the targeting scope of tumor antigens and improving the efficacy of traditional antibody-based therapeutics. Consequently, this review will focus on this emerging field and discuss related research advances. We introduce the classification, characteristics, and clinical applications of bsAbs, the theoretical basis for targeting intracellular antigens, delivery systems of bsAbs, and the latest preclinical and clinical advances of bsAbs targeting several intracellular oncotargets, including those of cancer-testis antigens, differentiation antigens, neoantigens, and other antigens. Moreover, we summarize the limitations of current bsAbs, and propose several potential strategies against immune escape and T cell exhaustion as well as some future perspectives. Highlights: Bispecific antibodies (BsAbs)-based therapeutics are promising in cancer immunotherapy. A large proportion of tumor antigens are intracellular. BsAbs targeting intracellular tumor antigens have raised much attention. Several potential strategies are proposed for T cell exhaustion.